(3GdefbP ef GdVdGd hGdeaUM Yf GdCMhGds - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi jaJJM HMeOg cd QSGdI hebGdI CeG HYO , abO SCdJfi CjgG GdCN ai GdOjf Cf CHK dc ZGjI GdYdhe hCSQGQgG hZGjI GdePGgH hCZhGQgG s
(3BNQgG (B:s
(3aJacQhG ai fUMJfGdcf , heG MGhdfGg ef GdEfbGP dce ef GdVdGd hGdEaUGM dce Yf GdCMhGd , aajg TaGA def CUZi , hOGe Ydi JPcQg hhYi Je GdcJGH GdeHGQc HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi ghGeTgG JUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds